Pengembangan Media Komunikasi, Informasi, dan Edukasi Kesehatan Bagi Masyarakat Daerah Bencana Gunung Berapi di Kabupaten Sleman, Yogyakarta - Oktarina Mugeni Sugiharto (Fakultas Kedokteran Universitas Gadjah Mada, 2012)
Background: Geographically Indonesia is one country that exists within the ring of volcanoes of the world (ring of fire) which has 130 active volcanoes (including Mount Bromo, Mount Merapi, Mount Karakatau, etc.). These volcanoes stretches 7000 kilometers form the volcanic belt of Aceh to Sulawesi Utara. This study aims to promote communication media, information and education (IEC) for public health in the affected areas EC Media, Disasters, VolcanoesMethod Descriptive research methods. Primary data collection carried out by a structured questionnaire and to dig deeper conducted Focus Group Discussion (FGD) on the stakeholders at the Provincial Health Office, District Health Office, Health Center, Head, The Village, religious leaders and local community leadersResults: The results showed that the media are used for special education counseling volcanic disaster areas of health does not exist, only the use of masks and counseling about health behavior. Because the volcanic disaster in just a few districts only, so there is no media in particular. Knowledge of respondents in the area of Mount Merapi in Sleman of the status of the volcano most of the 57% did not know and only 43% know the right way. Mortality / death rate due to volcanic disaster of the population according to the Lahore district health department in November 2010 as many as 201 people. For the majority of deaths due to hot lava.Conclusion: In order to support the Act No. 24 of 2007 on disaster-prone communities are entitled to obtain information, education/training and skills in the face of catastrophic volcanic eruption, and the Health Act No. 36 of 2009 Section 7 reads every person is entitled to receive health information and education regarding the balanced and responsible, it is suggested that this media can be applied in all health centers especially in the area of volcanic disaster.Keywords: IEC media, disasters, volcanoes